A User Manual to Measure Gas Diffusion Kinetics in Plants: Pneumatron Construction, Operation, and Data Analysis - Trabi, Christophe L.; Pereira, Luciano; Guan, Xinyi; Miranda, Marcela T.; Bittencourt, Paulo R. L.; Oliveira, Rafael S.; Ribeiro, Rafael V.; Jansen, Steven (Frontiers in Plant Science, 2021)
The Pneumatron device measures gas diffusion kinetics in the xylem of plants. The device provides an easy, low‐cost, and powerful tool for research on plant water relations and gas exchange. Here, we describe in detail how to construct and operate this device to estimate embolism resistance of angiosperm xylem, and how to analyse pneumatic data. Simple and more elaborated ways of constructing a Pneumatron are shown, either using wires, a breadboard, or a printed circuit board. The instrument is based on an open-source hardware and software system, which allows users to operate it in an automated or semi-automated way. A step-by-step manual and a troubleshooting section are provided. An excel spreadsheet and an R-script are also presented for fast and easy data analysis. This manual aims at helping users to avoid common mistakes, such as unstable measurements of the minimum and maximum amount of gas discharged from xylem tissue, which has major consequences for estimating embolism resistance. Major advantages of the Pneumatron device include its automated and accurate measurements of gas diffusion rates, including highly precise measurements of the gas volume in intact, embolised conduits. It is currently unclear if the method can also be applied to woody monocots, gymnosperm species that possess torus-margo pit membranes, or to herbaceous species.